2006
DOI: 10.1002/bmc.729
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic study of free‐form sinomenine in rat skin by microdialysis coupled with liquid chromatography–electrospray mass spectrometry

Abstract: Sinomenine (7,8-didehydro-4-hydroxy-3,7-dimethoxy-17-methylmorphinan-6-one) is a pure alkaloid extracted from the Chinese medical plant. In this report a liquid chromatography-electrospray mass spectrometry (LC-ESI-MS) method with in vivo microdialysis for the pharmacokinetic study of free-form sinomenine in rat skin has been developed. A microdialysis probe was surgically implanted into the subcutaneous tissue of the rats and an isotonic phosphate buffer (PBS) was used as the perfusion medium. Samples were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
2
1
Order By: Relevance
“…Microdialysis is a reliable and useful technique for investigation of percutaneous absorption and dermal metabolism. For instance, two unknown substances, suspected to be the metabolites of sinomenine, mostly demethyl and hydroxylated derivatives of sinomenine were found in skin microdialysates from the rats which were administered sinomenine [23,24]. Our results, although determined only in five rats, showed that the extent of metabolised OMT in the skin was rather low in relation to the amount which penetrated through the skin.…”
Section: Lc-ms/ms Analysis Of Omt and Its Metabolite Mt In Rat Biologcontrasting
confidence: 53%
“…Microdialysis is a reliable and useful technique for investigation of percutaneous absorption and dermal metabolism. For instance, two unknown substances, suspected to be the metabolites of sinomenine, mostly demethyl and hydroxylated derivatives of sinomenine were found in skin microdialysates from the rats which were administered sinomenine [23,24]. Our results, although determined only in five rats, showed that the extent of metabolised OMT in the skin was rather low in relation to the amount which penetrated through the skin.…”
Section: Lc-ms/ms Analysis Of Omt and Its Metabolite Mt In Rat Biologcontrasting
confidence: 53%
“…Several liquid-liquid extractions or protein precipitation procedures [14][15][16][17][18][19][20][21][22] were exploited for plasma sample preparation. Acetonitrile, methanol and 7% perchloric acid were chosen and tested for protein precipitation because of high throughput characteristics and the suitable sensitivities obtained.…”
Section: Lc/ms/ms Optimization and Sample Preparationmentioning
confidence: 99%
“…Furthermore, the lower limits of quantitation (LLOQ) of these methods in a range of 6-320 ng/mL were not suitable for sinomenine pharmacokinetic study. Some more sensitive methods using LC/MS have been reported to detect this drug in rat's brain [20] or skin [21]. Only one study using ion trap mass spectrometry has been published for the determination of sinomenine in human plasma with an LLOQ of 0.5 ng/mL [22], but the analyses were performed only with spiked plasma samples so pharmacokinetic parameters were not available.…”
Section: Introductionmentioning
confidence: 98%